New prognosis score including absolute lymphocyte/monocyte ratio, red blood cell distribution width and beta‐2 microglobulin in patients with diffuse large B‐cell lymphoma treated with R‐CHOP: Spanish Lymphoma Group Experience (GELTAMO) - Bento, Leyre; Díaz‐López, Antonio; Barranco, Gilberto; Martín‐Moreno, Ana M.; Baile, Mónica; Martín, Alejandro; Sancho, Juan M.; García, Olga; Rodríguez, Mario; Sánchez‐Pina, Jose M.; Novelli, Silvana; Salar, Antonio; et al. (British journal of haematology, 2020)
Summary The International Prognostic Index (IPI) is the most widely used score for non‐Hodgkin lymphoma but lacks the ability to identify a high‐risk population in diffuse large B‐cell lymphoma (DLBCL). Low absolute lymphocyte count and high monocytes have proved to be unfavourable factors. Red‐cell distribution width (RDW) has been associated with inflammation and beta‐2 microglobulin (B2M) with tumour load. The retrospective study included 992 patients with DLBCL treated with R‐CHOP. In the multivariate analysis, age, Eastern Cooperative Oncology Group performance status (ECOG‐PS), stage, bulky mass, B2M, RDW, and lymphocyte/monocyte ratio (LMR) were independently related to progression‐free survival (PFS). A new prognosis score was generated with these variables including age categorized into three groups (0, 1, 2 points); ECOG ≥ 3–4 with two; stage III/IV, bulky mass, high B2M, LMR < 2·25 and RDW > 0·96 with one each; for a maximum of 9. This score could improve the discrimination of a very high‐risk subgroup with five‐year PFS and overall survival (OS) of 19% and 24% versus 45% and 59% of R (revised)‐IPI respectively. This score also showed greater predictive ability than IPI. A new score is presented including complete blood cell count variables and B2M, which are readily available in real‐life practice without additional tests. Compared to R‐IPI, it shows a more precise high‐risk assessment and risk discrimination for both PFS and OS.